Rekomendasi Teknis Budidaya Tanaman Padi Terhadap Petani di Desa Sambirejo Timur, Deli Serdang - Fahri, Romi; Wardani, Tuti; Yanti, Sisilia Florina (PATRIOTIKA: Jurnal Inovasi dan Pemberdayaan Masyarakat, 2025)
The Tri Dharma of Higher Education is a concept that guides higher education institutions in carrying out their duties and functions. This concept consists of three pillars, namely: Education and teaching, Research, and Community Service. Community service activities for lecturers are an effort to carry out one of the duties of the Tri Dharma of Higher Education. The community service carried out in this activity was related to Technical Recommendations for Crop Cultivation to Increase Rice Production among Farmers in Sambirejo Timur Village, Percut Sei Tuan District, Deli Serdang Regency. This activity aimed to implement the Tri Dharma of Higher Education for lecturers in order to contribute theoretical and practical agricultural knowledge to farmers. This community service, which is a collaboration between two lecturers from Nusa Cendana University and Nahdlatul Ulama University of North Sumatra (UNUSU), provides farmers with the knowledge they need to increase rice production. The expected outcome of this activity is that farmers will understand the factors of crop production so that in the future they can analyse the crop cultivation problems they face and solve them independently.